ORGANIZATIONAL COMMUNICATION MODEL IN REGIONAL GOVERNMENT OF SIDOARJO DISTRICT IN MAKING LOCAL REGOLATION - Retnowati, Nova (Advances in Social Sciences Research Journal, 2019)
The main key to the implementation of Regional Government (Pemda) in the making of local regulations (Perda) is the well-established organizational communication among the management of the management, so that it can equalize perceptions to support and accelerate development programs in the region. With harmonious organizational communication can be avoided slow process, long-winded, so that it is not efficient which results in the direction of regional development to be inconsistent (Sadu Wasistiono, 2010: 42). For this reason, local government managers should have a partnership and equal relationship. This partnership relationship is important in the process of making a Perda. This study uses a qualitative approach that is focused on identifying the dominant factors that can facilitate the communication of local government organizations in the process of making Perda. Data collection techniques use purposive methods and domain analysis. Thus, this research is expected to be studied in a normative, sociological manner that is comprehensive and holistic. This study resulted in the finding of 4 (four) dominant factors in organizational communication in the Sidoarjo Regency Government which became a catalyst in the implementation of local democracy, namely facilities, budget support, staff competence, and good relations with mass media. Through classifying the flow of communication based on the domain that has been established, the research team can finally build a communication model of the Sidoarjo Regency Government organization in the process of making the Perda. The main key to the implementation of Regional Government (Pemda) in the making of local regulations (Perda) is the well-established organizational communication among the management of the management, so that it can equalize perceptions to support and accelerate development programs in the region. With harmonious organizational communication can be avoided slow process, long-winded, so that it is not efficient which results in the direction of regional development to be inconsistent (Sadu Wasistiono, 2010: 42). For this reason, local government managers should have a partnership and equal relationship. This partnership relationship is important in the process of making a Perda. This study uses a qualitative approach that is focused on identifying the dominant factors that can facilitate the communication of local government organizations in the process of making Perda. Data collection techniques use purposive methods and domain analysis. Thus, this research is expected to be studied in a normative, sociological manner that is comprehensive and holistic. This study resulted in the finding of 4 (four) dominant factors in organizational communication in the Sidoarjo Regency Government which became a catalyst in the implementation of local democracy, namely facilities, budget support, staff competence, and good relations with mass media. Through classifying the flow of communication based on the domain that has been established, the research team can finally build a communication model of the Sidoarjo Regency Government organization in the process of making the Perda.